Selective sorting of polymers with different terminal groups using metal-organic frameworks - Benjamin Le Ouay (Nature Portfolio, 2018)
The separation of high molecular weight polymers composed of the same number of monomeric units remains highly challenging. Here, the authors show that efficient separation and purification of mixtures of polymers that differ only by their terminal groups can be achieved through polymer threading in metal-organic framework channels.